Toxicological, Antidiarrheal and Spasmolytic Activities of Solanum paniculatum - Clementino-Neto, José; Pereira, Joedna C.; Vasconcelos, Luiz H. C.; de Souza, Iara L. L.; Silva, Anne D. S.; Silva, Telma M. G.; Ramos, Natalia S. M.; Pessôa, Hilzeth L. F.; Silva, Tania M. S.; da Silva, Bagnólia A.; de Cavalcante, Fabiana A. (Planta Medica, 2016)
Solanum paniculatum is popularly known as “jurubeba-verdadeira”. In folk medicine, its roots, stems, and leaves are used as tonics, anti-inflammatories, carminatives, diuretics, and for gastrointestinal disorders. This species is listed in the Brazilian Pharmacopoeia and belongs to the “Relação Nacional de Plantas Medicinais de Interesse ao SUS”. Based on folk medicine data of the Solanum genus, we decided to investigate whether the crude ethanol extract from S. paniculatum aerial parts presents toxicological, antidiarrheal, and spasmolytic activities. The crude ethanol extract from S. paniculatum aerial parts did not produce in vitro or in vivo toxicity and showed dose-dependent antidiarrheal activity, inhibiting equipotently both the defecation frequency (ED50 = 340.3 ± 35.1 mg/kg) and liquid stool formation (ED50 = 370.1 ± 19.4 mg/kg) in mice. Conversely, the crude ethanol extract from S. paniculatum aerial parts did not inhibit normal intestinal transit, even though it has shown a dose-dependent reduction of both the castor oil-induced intestinal transit (Emax = 36.9 ± 1.3 %, ED50 = 242.0 ± 8.6 mg/kg) and intestinal fluid content (Emax = 74.8 ± 2.4 %, ED50 = 328.9 ± 15.9 mg/kg). Additionally, the crude ethanol extract from S. paniculatum aerial parts was approximately 2-fold more potent in antagonizing the phasic contractions induced with histamine (IC50 = 63.7 ± 3.5 µg/mL) than carbachol 10−6 M (IC50 = 129.3 ± 14.1 µg/mL). Therefore, we concluded that the crude ethanol extract from S. paniculatum aerial parts presents antidiarrheal activity in mice related to the inhibition of small intestinal motility and secretion as well as nonselective spasmolytic activity on the guinea pig ileum.
Keywords: Solanum paniculatum; Solanaceae; toxicological activity; antidiarrheal effect; spasmolytic action